National Disaster Policy: Criticism of the State's Response to the Disaster in West Sumatra - Muhammad Zikri; Ashri Ramadhan (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2026)
The determination of national disaster status in Indonesia is frequently misconstrued as a purely technocratic decision governed by objective metrics of casualties and material loss. This article challenges that positivist assumption by analyzing the state's refusal to elevate the status of the May 2024 cold lava flood (galodo) in West Sumatra, despite catastrophic damage that exceeded regional fiscal capacities. Utilizing a Critical Policy Analysis (CPA) framework synthesized with Joel Migdal's State-in-Society theory, this study demonstrates that disaster status determination functions as a political mechanism for fiscal preservation and the management of central-regional power relations. The analysis reveals three primary policy patterns: (1) the discursive manipulation of legal definitions regarding